Flash Pyrolysis – Synthetic and Mechanistic Aspects - Curt Wentrup (CHIMIA)
Some examples of synthetically useful flash pyrolysis reactions are presented, and the reaction mechanisms are discussed. Cyanocyclopentadienes, -indenes, and -pyrroles are produced by pyrolysis of the appropriate triazoloarenes or isatins, or as the end products of carbene-nitrene rearrangements. Fulvenallene is formed from benzocyclopropene, phthalide, phenyldiazomethane, 7-norbornadienyl acetate, and other precursors. Cyclopropa[b]naphthalene and cyclopropa[b]-1,6-methano 10]-annulene yield 2-ethynylindene and acenaphthene, respectively. α-Coumaranone yields fulvene. Pyrido- and pyrimido[2,1-a]isoindoles are obtained by carbene-carbene rearrangements, starting from v-triazolo[1,5-a]-azines. The pyrolysis of 5-aryltetrazoles leads to diazocompounds, triazoloazines, or carbenes. 2,5-Diaryltetrazoles give indazoles or fluorenes, also obtainable from 2,4-diaryl-1,3,4-oxa-diazolin-5-ones. Arylacetylenes, five- and six-membered hetaryl-acetylenes, isocyanamines, and ketenimines are formed by pyrolysis of appropriately 4-substituted isoxazol-5-ones.